Reframing labour market mobility in global finance: Chinese elites in London’s financial district - Hall, Sarah (Taylor & Francis, 2018)
In this paper, I use the case of elite Chinese financial mobility to London’s financial district to argue that comparatively neglected forms of elite financial migration from beyond the Global North provide important insights into the changing geographical form, and labour market practices within, leading international financial centres. By reporting on original empirical research, two main findings emerge. First, Chinese financial mobility to London has a distinctive geographical footprint in terms of both financial services activity and residential choices. Second, the rationale behind elite Chinese financial mobility to London cannot be fully explained by existing work on highly skilled migration and expatriation that emphasises the economic imperatives driving mobility. In response, I argue that work on elite mobility requires a fuller engagement with wider debates in economic geography that examine the interdependencies and inter-relationships between states and markets. These findings raise important questions surrounding the durability of Chinese finance in London, its relationship to global finance in London more generally, and wider understandings of elite financial labour markets.